Identification and Pleiotropic Effect Analysis of GSE5 on Rice Chalkiness and Grain Shape - Jiang, Liangrong; Zhong, Hui; Jiang, Xianbin; Zhang, Jiaoping; Huang, Rongyu; Liao, Furong; Deng, Yaqin; Liu, Qingqing; Huang, Yumin; Wang, Houcong; Tao, Yi; Zheng, Jingsheng (Frontiers in Plant Science, 2022)
Chalkiness is one of several major restricting factors for the improvement of rice quality. Although many chalkiness-related quantitative trait loci have been mapped, only a small number of genes have been cloned to date. In this study, the candidate gene GSE5 of a major quantitative trait locus (QTL) for rice chalkiness, qDEC5, was identified by map-based cloning. Phenotyping and haplotype analysis of proActin:GSE5 transgenic line, gse5-cr mutant, and 69 rice varieties further confirmed that GSE5 had the pleiotropic effects and regulated both chalkiness and grain shape. Genetic analysis showed GSE5 was a dominant gene for grain length and a semi-dominant gene for grain width and chalkiness. The DNA interval closely linked to GSE5 was introgressed to Zhenshan 97B (ZB) based on molecular marker-assisted selection, and the improved ZB showed lower chalkiness and longer but smaller grains, which showed that GSE5 played an important role in breeding rice varieties with high yield and good quality. Transcriptomics, proteomics, and qRT-PCR analyses showed that thirty-nine genes associated with carbon and protein metabolism are regulated by GSE5 to affect the formation of chalkiness, including some newly discovered genes, such as OsCESA9, OsHSP70, OsTPS8, OsPFK04, OsSTA1, OsERdj3A, etc. The low-chalkiness lines showed higher amino sugar and nucleotide sugar metabolism at 10 days after pollination (DAP), lower carbohydrate metabolism at 15 DAP, and lower protein metabolism at 10 and 15 DAP. With heat shock at 34/30°C, rice chalkiness increased significantly; OsDjC10 and OsSUS3 were upregulated at 6 and 12 DAP, respectively, and OsGSTL2 was downregulated at 12 DAP. Our results identified the function and pleiotropic effects of qDEC5 dissected its genetic characteristics and the expression profiles of the genes affecting the chalkiness formation, and provided a theoretical basis and application value to harmoniously pursue high yield and good quality in rice production.